Factors Influencing Interest in Buying Ornamental Plants In Indralaya City, Ogan Ilir Regency - Mahcfiroh Akbarika; septianita septianita; ema pusvita (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2026)
This study aims to analyze the factors that affect the interest in buying ornamental plants in Indralaya City, Ogan Ilir Regency. The main focus of the study was three independent variables, namely ornamental plant prices, consumer income, and taste, which were measured using indicators of preference for flowering and non-flowering plants. The method used is a quantitative approach with logistic regression analysis techniques. Data was collected through a survey with a questionnaire of 40 respondents who were selected purposively. The results of the analysis showed that simultaneously, the three variables (price, income, and taste) had a significant effect on the buying interest of ornamental plants. Partially, the price and income variables had a significant effect on the confidence level of 95% (α = 0.05), while the taste variable had a significant effect on the level of 10% (α = 0.10). The coefficient of determination (Nagelkerke R²) of 36.2% indicates that the model is able to explain the dependent variables quite well. From these results, it can be concluded that price and income are the main factors in the decision to purchase ornamental plants in Indralaya City, while taste still makes a positive contribution. This research provides implications for ornamental plant business actors in formulating marketing strategies based on purchasing power and local consumer preferences. Keywords: buying interest, income, price, ornamental plants, taste